2021
DOI: 10.1049/smt2.12080
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling of rate gyros based on fully overlapping Allan variance

Abstract: Angular random walk and rate random walk are two dominant random noise components which are inherent in almost gyroscopes. Therefore, modelling these noise components accurately is very important. Here, a modified algorithm is proposed for estimating the two random noise components accurately. Up to now, the statistical modelling of the two random noise components has been conducted by the best linear unbiased estimator, which is based on the formulae for mean, variance and covariance of non‐overlapping Allan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, parameters are usually estimated by performing linear regression of (visually) identified linear regions in such log–log plots. Further research on this principle can be found in [ 8 , 9 , 10 , 25 , 26 ]. A GMWM-based algorithm can be considered as a further extension of AV because they both identify and quantify the different noise terms that exist in inertial sensor data.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, parameters are usually estimated by performing linear regression of (visually) identified linear regions in such log–log plots. Further research on this principle can be found in [ 8 , 9 , 10 , 25 , 26 ]. A GMWM-based algorithm can be considered as a further extension of AV because they both identify and quantify the different noise terms that exist in inertial sensor data.…”
Section: Methodsmentioning
confidence: 99%
“…Equation (10) shows derived releasing and capturing bounds, which are used in the following to extract power spectrum density (PSD) and model the LFN. The noise PSD based on carriers number fluctuations [18] is expressed by…”
Section: Releasing and Capturing Boundsmentioning
confidence: 99%
“…Lines 7 to 13 are the release process in which the releasing probability is calculated for each carrier. If this probability is greater than the probability of Equation (10), it means the carrier has been released.…”
Section: Lfn Modelling Using Device-specific and Probabilistic Inputsmentioning
confidence: 99%
See 2 more Smart Citations